Infection Following Internal Fixation Of Closed Fractures - Mohd Yusof, Nazri; Zulkifly, Ahmad Hafiz; Khalid, Kamarul Ariffin; Zakaria@Mohamad, Zamzuri; Che Ahmad, Aminudin; Mohamed Amin, Mohamed Azril; Awang, Mohd Shukrimi (Faculty of Medicine, International Islamic University Malaysia, 2006)
This is a prospective study on infection following fixation of closed fractures done in Hospital Tengku Ampuan Afzan ,Kuantan from May 2003 to May 2005. There were 23 cases in this study. The mean age of patient was 32.9 years (range 15 to 77). Twenty one were males and 2 females. Twenty (87%) infections occurred in the lower limb and only 3(13%) occurred in the upper limbs. Twenty two patients (91%) had plating done for the fracture. Infection following internal fixation is commonly a deep seated (96%) and florid (78%) infection in which 70% occur after the surgical wound has healed. Staphylococcus aureus is the commonest organism isolated in which 43% are Methicillin resistant (MRSA). Overall infection caused by gram negative organisms is more common than gram positive organisms